2021
DOI: 10.3390/pharmaceutics13111829
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Engineered Nanoparticles for Breast Cancer Therapy

Abstract: Breast cancer (BC) is the second most common cancer in women globally after lung cancer. Presently, the most important approach for BC treatment consists of surgery, followed by radiotherapy and chemotherapy. The latter therapeutic methods are often unsuccessful in the treatment of BC because of their various side effects and the damage incurred to healthy tissues and organs. Currently, numerous nanoparticles (NPs) have been identified and synthesized to selectively target BC cells without causing any impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 221 publications
(274 reference statements)
0
25
0
Order By: Relevance
“…The poor oral bioavailability of PPN corresponds to its high lipophilicity and very limited water solubility (40 μg/mL) [ 13 ]. By considering the above facts, formulation scientists across the world focus on the preparation of novel formulations based on nanotechnology to improve oral bioavailability of lipophilic compounds by increasing aqueous solubility to improve its efficacy against BC [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The poor oral bioavailability of PPN corresponds to its high lipophilicity and very limited water solubility (40 μg/mL) [ 13 ]. By considering the above facts, formulation scientists across the world focus on the preparation of novel formulations based on nanotechnology to improve oral bioavailability of lipophilic compounds by increasing aqueous solubility to improve its efficacy against BC [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional cancer treatment methods including chemotherapy, radiotherapy and surgery have serious side effects or cannot completely eliminate the tumors. [1][2][3] As a modern technology combining the characteristics of nanomaterials and the therapeutic effects of payload, nanotechnology has been extensively investigated and has been considered to revolutionize the traditional treatment of cancer. [4][5][6] Until now, a few of nanoagents have been approved by the Food and Drug Administration (FDA) for clinical treatment of cancer or are in different stages of clinical studies, such as Doxil ® , Abraxane ® , NanoTherm ® , and Atu027.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the presence of a negative carboxyl group increases the surface charge of nanoparticles and enhances their uptake. However, (Hea-Young Cho 2015; Kumar Ganesan et al 2021) reported that the surface targeting vector (Folate) may precisely target the drug on cancer cells, despite the fact that it retains its ability to bind to receptors after drug conjugation and attaches to the receptors located within caveolae (Mi et al 2011), and it is internalized through the endocytosis pathway and increases the availability of the drug in the cancer cells, which leads to a decrease in cell viability.…”
Section: In Vitro Cell Line Studymentioning
confidence: 99%